Case report: LMNB1 duplication-mediated autosomal dominant adult leukodystrophy in a Chinese family and literature review of Chinese patients - Jiang, Yumeng; Han, Lu; Li, Yaqi; Zhao, Zhihong; Xin, Zikai; Zhu, Zilong (Frontiers in Neuroscience, 2025)
Adult-onset autosomal dominant leukodystrophy (ADLD) is a rare, slowly progressive, and fatal neurodegenerative disorder characterized by central nervous system white matter loss due to LMNB1 gene abnormalities encoding laminB1. However, not all LMNB1 mutations lead to ADLD. Currently, two genetic alterations have been identified in association with the pathogenesis of ADLD: LMNB1 gene tandem duplication and LMNB1 gene upstream deletions. We report a case of a 60-year-old man diagnosed with ADLD, with pyramidal tract dysfunction and autonomic abnormalities as the main clinical manifestations. MRI revealed bilateral symmetric high signal intensities in the white matter of the medulla oblongata, middle cerebellar peduncles, cerebral peduncle, periventricular white matter, centrum semi vale, and the pressure region of the corpus callosum. Whole exome sequencing results indicated 73.6Kb duplicate copy number variation signals in the 5q23.2 region of the proband’s chromosome. The Multiplex ligation-dependent probe amplification (MLPA) experiment results indicate recurrent mutations across all exons (exon1–11) of the LMNB1 gene. This is the eighth ADLD pedigree from China. We conducted a literature review of all ADLD pedigrees in China and summarized the characteristics of Chinese patients with ADLD to raise awareness of ADLD disease.